2008
DOI: 10.1111/j.1365-246x.2008.03720.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface wave tomography of the western United States from ambient seismic noise: Rayleigh and Love wave phase velocity maps

Abstract: S U M M A R YWe present the results of Rayleigh wave and Love wave phase velocity tomography in the western United States using ambient seismic noise observed at over 250 broad-band stations from the EarthScope/USArray Transportable Array and regional networks. All available threecomponent time-series for the 12-month span between 2005 November 1 and 2006 October 31 have been cross-correlated to yield estimated empirical Rayleigh and Love wave Green's functions. The Love wave signals were observed with higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
673
2
11

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 696 publications
(702 citation statements)
references
References 29 publications
16
673
2
11
Order By: Relevance
“…In this approach, the zero crossings of the real part of the cross-correlation spectrum are evaluated to derive the phase-velocity dispersion. Importantly, this means that the Green's function's amplitude does not have to be reconstructed, which is the case when phase is to be determined by analysis of time-domain traces (Bensen et al 2007;Lin et al 2008;Zhou et al 2012;Verbeke et al 2012). We verify that our algorithm can successfully measure the phase velocity of both Love and Rayleigh waves from ambient noise.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…In this approach, the zero crossings of the real part of the cross-correlation spectrum are evaluated to derive the phase-velocity dispersion. Importantly, this means that the Green's function's amplitude does not have to be reconstructed, which is the case when phase is to be determined by analysis of time-domain traces (Bensen et al 2007;Lin et al 2008;Zhou et al 2012;Verbeke et al 2012). We verify that our algorithm can successfully measure the phase velocity of both Love and Rayleigh waves from ambient noise.…”
mentioning
confidence: 74%
“…Consequently, this issue is often ignored when extracting Love waves (e.g. Lin et al 2008;Ekström 2014). However, Fig.…”
Section: Horizontal Components (Rayleigh and Love Waves)mentioning
confidence: 99%
“…[4] We closely follow the method described by Bensen et al [2007] and Lin et al [2008] to obtain traditional vertical-vertical ambient noise cross correlations using continuous data between year 2000 and 2009 for all available GSN stations. This method uses temporal normalization (using the running-absolute-mean over a 128 s time window of the 15 to 50 s bandpassed raw noise waveform) to suppress impulsive high-amplitude earthquake signals.…”
Section: Data and Resultsmentioning
confidence: 99%
“…While extracting surface waves is still the major application [e.g., Shapiro et al, 2005;Yao et al, 2006;Lin et al, 2008], several recent studies have also shown that extracting deep-penetrating body waves using seismic interferometry is possible [Poli et al, 2012;Lin et al, 2013;Nishida 2013;BouĂ© et al, 2013]. The body wave phases, however, remain relatively weak and array stacking techniques are needed to strengthen the signals.…”
Section: Introductionmentioning
confidence: 99%
“…The tomographic maps they produced agree well with the known geology and previous seismic studies in the region. Since then, surface wave tomography using interferometric Rayleigh and Love waves, commonly referred to as ambient noise tomography, has become an increasingly employed method to successfully produce subsurface velocity models on regional and continental scales in areas such as the United States (Bensen et al, 2008; Lin et al, 2008;Shapiro et al, 2005;Sabra et al, 2005b;Liang and Langston, 2008), Australia (Arroucau et al, 2010;Rawlinson et al, 2008;Saygin and Kennett, 2010), New Zealand (Lin et al, 2007;Behr et al, 2010), Antarctica (Pyle et al, 2010), Iceland (Gudmundsson et al, 2007), China (Zheng et al, 2008;Li et al, 2009;Zheng et al, 2010), South Africa , Europe (Villaseñ or et al, 2007;Yang et al, 2006), South Korea (Cho et al, 2007) the Tibetan Plateau (Yao et al, 2006(Yao et al, , 2008Li et al, 2009), and in this paper, Scotland.…”
Section: Ambient Noise Tomographymentioning
confidence: 99%